2008
DOI: 10.1111/j.1539-6924.2008.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risk on Machinery: A Field Evaluation Pilot Study of Risk Assessment

Abstract: A pilot evaluation of the ANSI B11-TR3 Machinery Risk Assessment/Risk Reduction (RA/RR) Guideline was conducted. The TR3 guideline was introduced into five companies on one machinery system in each company with a second machine system serving as a control. A pre-post investigation was performed with safety conditions measured pre and post in both treatment and control and with risk reduction score measured only in the treatment machine system. NIOSH provided a commercially available risk assessment software to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This applies to hazards at the level of: mechanical, electrical, thermal, noise hazard or the properties of processed materials. If there is a risk that cannot be eliminated at this level, the manufacturer applies additional protective measures such as covers and protective devices (Etherton, 2008;Mössner, 2012). The above activities never reduce the risk to zero, there is always a residual risk, therefore manufacturers is obliged to inform and warn in the operating instructions (through appropriate markings and pictograms).…”
Section: Direct Requirements For the Machines Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…This applies to hazards at the level of: mechanical, electrical, thermal, noise hazard or the properties of processed materials. If there is a risk that cannot be eliminated at this level, the manufacturer applies additional protective measures such as covers and protective devices (Etherton, 2008;Mössner, 2012). The above activities never reduce the risk to zero, there is always a residual risk, therefore manufacturers is obliged to inform and warn in the operating instructions (through appropriate markings and pictograms).…”
Section: Direct Requirements For the Machines Safetymentioning
confidence: 99%
“…The analysis and risk assessment is the most important element of the entire process of ensuring machine safety (Hietikko et al, 2011;Etherton, 2008). The risk analysis is carried out by inspecting the machine, focusing on: detection of existing threats and calculation of the HRN index for them, checking compliance with the directives, current standards and regulations, analysis of electrical documentation, safety instructions.…”
Section: Recommendations For the Machine Designer/constructormentioning
confidence: 99%
“…Machine-related accidents would thus be responsible for one third of the deaths at work in the United State (Etherton et al, 2008). More recently, the US Bureau of Labor Statistics reported 717 deaths associated with machinery in 2013 (US Bureau of Labor Statistics, 2014).…”
Section: Safety Of Machinerymentioning
confidence: 99%
“…He concluded that some uncertainty was inherent in risk estimation, but industry-specific guidelines could help improve this process. Etherton, Main, Cloutier, et al conducted a field evaluation of the risk assessment process [10] proposed in the technical report ANSI B11.TR3:2000 [11]. However, their study focused on the benefits of the entire risk assessment process and not on risk estimation itself.…”
Section: Previous Studies On Risk Estimationmentioning
confidence: 99%